Optimization of modified fenton (FeGAC/ H2O2) pretreatment of antibiotics - Affam, A.C. (Universiti Putra Malaysia Press, 2014)
The study examined modified Fenton (FeGAC/H2O2) pretreatment of the antibiotics amoxicillin and cloxacillin in aqueous solution for biological treatment. The treatment was optimized by the response surface methodology (RSM). The optimum operating conditions at pH3 were H2O2/COD molar ratio 2.0, FeGAC dose 3.5 g/L and reaction time 90 min for 87.53 removal of COD, 78.01 removal of TOC, and 98.24 removal of NH3-N. Biodegradability (BOD5/COD ratio) improved from zero to 0.36, indicating the effluent was amenable to biological treatment. Meanwhile, FTIR spectra indicated degradation of the antibiotics. Compared with Fenton or photo-Fenton, modified Fenton (FeGAC/H2O2) was more effective in the pre-treatment of the antibiotics amoxicillin and cloxacillin in aqueous solution for biological treatment. Â© 2014 Universiti Putra Malaysia Press.